Red Flags Associated With Knowledge Of Speech And Language Disorders Among Special Educators - Shah, Syed Tariq; Mumtaz, Nazia; Saqulain, Ghulam (Journal of Rawalpindi Medical College, 2023)
Objective: To explore the knowledge about speech and language disorders among special educators of Army schools in Pakistan in association with qualification and experience. Methods: This cross-sectional descriptive study using convenience sampling was conducted at Isra Institute of Rehabilitation Sciences, Isra University from May to October 2017 and comprised of two phases. Phase 1 included the construction & pilot testing of a questionnaire utilizing a sample of N=20 educators and Phase 2 included the main study with N=100 educators of both genders from schools of Army Special Education Academy, Sir Syed School and College of Special Education and Aghosh Special Education Centre Kharian Cantonment. The sample educators included both genders, dealing with children with intellectual and hearing impairment. SPSS Version 20 was used for data analysis. Results: To assess the knowledge of the educators, a specially structured questionnaire with Cronbach’s alpha reliability coefficient of 0.79 was applied to a sample with a mean age of 32.70±6.92 years with the majority of 85(85%) being female educators. The study revealed good knowledge of educators with a total mean score of 69.70±10.61 and a significant (p=0.000) association of knowledge of educators with the highest scores for those with Masters Qualification (73.15±7.68). However, no significant association between gender (p=0.151) and work experience of educators (p=0.093) was noted, though the scores were higher for educators with 11-15 years of experience. Conclusion: The study concludes good knowledge of special educators about speech and language disorders with some red flags including the significant association of knowledge with qualification with master (special education) qualification presenting with a higher level of knowledge. However, work experience and gender did not reflect any significant association with the knowledge of educators. Keywords: Hearing Impairment, Intellectual Impairment, Special Education, Speech Language Disorders